Exploring The Impact of Deep Learning Approaches on Geography Education: Student Perceptions and Educational Implications - Syafril; Junaidin (Jurnal Penelitian Pendidikan IPA, 2025)
This study addresses the gap in understanding the effectiveness of deep learning approaches in geography education, particularly in higher education contexts where such methods are not yet fully integrated. The aim of this study was to explore students' perceptions of deep learning in geography courses, focusing on its impact on their understanding of the subject, critical thinking, student engagement, and the role of technology. A quantitative descriptive research design was employed, utilizing a structured questionnaire administered to 100 geography students from a university in Indonesia. The questionnaire explored five key areas: understanding of deep learning, deep learning-based instructional processes, student engagement, the use of technology, and the development of higher-order thinking skills. The results showed that students perceived deep learning as effective in enhancing their understanding of geography, improving critical thinking skills, and increasing engagement in the learning process. Students also recognized the importance of integrating technology, such as digital tools and geospatial data, in fostering deeper learning experiences. However, while students expressed positive perceptions, the study highlighted the need for further professional development for educators in applying deep learning strategies effectively. In conclusion, deep learning has the potential to significantly enhance geography education by fostering deeper engagement, critical thinking, and the use of technology. It is recommended that higher education institutions invest in training faculty members to integrate deep learning methods into their teaching practices and that future research explore the long-term effects of deep learning on academic performance and real-world applications in geography.